2010
DOI: 10.1111/j.1365-2672.2009.04482.x
|View full text |Cite
|
Sign up to set email alerts
|

Damage of Escherichia coli membrane by bactericidal agent polyhexamethylene guanidine hydrochloride: micrographic evidences

Abstract: Aims:  The purpose of this study was to provide micrographic evidences for the damaged membrane structure and intracellular structure change of Escherichia coli strain 8099, induced by polyhexamethylene guanidine hydrochloride (PHMG). Methods and Results:  The bactericidal effect of PHMG on E. coli was investigated based on β‐galactosidase activity assay, fluorescein‐5‐isothiocyanate confocal laser scanning microscopy, field emission scanning electron microscopy and transmission electron microscopy. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
93
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 45 publications
5
93
1
2
Order By: Relevance
“…Our research results showed that S. aureus formed less biofilm than E. coli. Research by Zhou et al [12] indicates that low PHMG concentrations only damaged the external structures of bacterial cell membrane. Das et al [13] determined the ability of E. coli and S. aureus to form biofilm on polymers with incorporated polyhexamethylene biguanide in the presence of acetic acid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research results showed that S. aureus formed less biofilm than E. coli. Research by Zhou et al [12] indicates that low PHMG concentrations only damaged the external structures of bacterial cell membrane. Das et al [13] determined the ability of E. coli and S. aureus to form biofilm on polymers with incorporated polyhexamethylene biguanide in the presence of acetic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Most AMMs (anti-microbial macromolecules) including PHMG have the charge and hydrophobicity moieties as anti-microbial peptides [22], and many researchers speculate that AMMs act by disruptive interaction on the lipid interface membrane as anti-microbial peptides, but there was a lack of experimental evidences on membrane disruption and their biological mechanism [22,23]. According to Zhou et al [12] and Linyan et al [24] the biocidal activity of PHMG may be related to its ability to damage the cell membrane. Most probably, PHMG first damages the outer membrane, and then higher concentrations result in damage to of the cell wall and cytoplasmic membrane [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AKWATON is a new colorless, odorless, non-corrosive antimicrobial product with excellent microbicidal power. Its antimicrobial activities have been widely documented [19,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that the cytoplasmic membrane disruption of bacteria cells induced by PHMG-membrane interactions is the main antibacterial mechanism by micrographic observations of Escherichia coli cells exposed to PHMG [9,16]. However, a detailed characterization of interactions between the guanidine hydrochloride polymer molecule and the phospholipid membrane has not yet been performed.…”
Section: Introductionmentioning
confidence: 99%